Inhibitory effects of Rhenium-188-labeled Herceptin on prostate cancer cell growth: A possible radioimmunotherapy to prostate carcinoma. (May 2013) - Wang, Hsin-Yi; Lin, Wan-Yu; Chen, Mei-Chih; Lin, Teh; Chao, Chih-Hao; Hsu, Fu-Ning; Lin, Eugene; Huang, Chih-Yang; Luo, Tsai-Yueh; Lin, Ho
Abstract Purpose: Herceptin is widely used in treating Her2-overexpressing breast cancer. However, the application of Herceptin in prostate cancer is still controversial. Our previous results have indicated the relevance of Her2 in the transition of the androgen requirement in prostate cancer cells. In this study, the effects of radioimmunotherapy against Her2 in prostate cancer were investigated. Materials and methods: DU145, an androgen receptor-negative prostate cancer cell line, was used in vitro and in vivo to evaluate the effects of Herceptin labeled with a beta emitter, Rhenium-188 (Re-188). Its effects on cell growth, extent of apoptosis, the bio-distribution of Re-188 labeled Herceptin (Re-H), and protein levels were determined. Results: Treatments with Re-188 and Re-H reduced the proliferation of DU145 cells in dose- and time-dependent manners compared to the Herceptin-treated group. Growth inhibition and apoptosis were induced after Re-H treatment; growth inhibition was more distinct in cells with high Her2/p-Her2 levels. Our in vivo xenograft studies revealed that Re-H treatment significantly retarded tumor growth and altered the levels of apoptosis-related proteins. The bio-distribution of Re-H in mice demonstrated a tissue-specific pattern. Importantly, the levels of p35 protein, which is related to cancer cell survival and invasion, dramatically decreased after Re-H treatment. Conclusions: Our data demonstrate that Re-188-labeled Herceptin effectively inhibited the growth of DU145 cells compared to the Herceptin- and Re-188-treated cohorts. This implies that targeting Her2 by both radio- and immuno- therapy might be a potential strategy for treating patients with androgen-independent prostate cancer.